Kajian kepuasan penumpang pengguna face recognition pada sistem boarding pass di Stasiun Madiun - Ependi, Ahmad; Aprilia, Nyimas Arnita; Derbyandika, Ramadian (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to evaluate passenger satisfaction with the use of Face Recognition technology in the boarding pass system at Madiun Station. This technology was adopted to improve the efficiency of the boarding process and reduce queues, but it still creates different perceptions among users regarding its convenience. The study used the SERVQUAL method to measure service quality with five main dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. Data was collected through questionnaires to 100 respondents, long-distance train users who boarded from Madiun Station. The results showed a gap between user expectations and system performance, especially in the Tangibles and Reliability dimensions. This study recommends improvements in the operation of Face Recognition technology and increased socialization to passengers to better understand and accept this system.